N-Aryl Arenedicarboximides as Tunable Panchromatic Dyes for Molecular Solar Cells - Zhi Cao; Premchendar Nandhikonda; Adriana Penuela; Stephanie Nance; Michael D. Heagy (International Journal of Photoenergy)
Three organic dyes designed as molecular dyads were prepared that feature a common naphthalimide acceptor and N-aryl donors. One of these incorporated an additional cyanoacrylic acid linker and conjugated thiophene bridge inserted between donor and acceptor groups. Electrochemical and photochemical characterizations have been carried out on nanocrystalline TiO2 dye-sensitized solar cells which were fabricated with these dyes as the sensitizing component. HOMO and LUMO energies were also calculated using TDDFT methods and validated by the cyclic voltammetry method. A key finding from this study indicates that computational methods can provide energy values in close agreement to experimental for the N-aryl-naphthalimide system. Relative to HOMO/LUMO energy levels of N719, the dyes based on naphthalimide chromophore are promising candidates for metal-free DSSCs.